Granular cell astrocytoma: Case report - Rohan Gupta; Supriya Gupta; Nathaniel Shapiro; Scott Rahimi; Suash Sharma (Elsevier, 2018)
Granular Cell Astrocytoma (GCA) is a rare astrocytic brain tumor histologically composed of plump astrocytic cells with abundant eosinophilic granular cytoplasm that exhibits immunoreactivity for GFAP and S100 proteins. It is associated with poor outcome often akin to glioblastoma despite its bland histologic appearance. We report a case of GCA in which neoplastic cells resembled macrophages on intra-operative frozen section and smear. Paraffin sections showed features of a granular cell astrocytoma, WHO grade IV, with diffuse immunohistochemical coexpression of GFAP and S100. No mutation of IDH1 or P53 was identified by immunohistochemistry; however, ATRX loss indicating mutation supported an astrocytic lineage. Additionally, sporadic weak cytoplasmic staining for CD68 and EMA and negative staining for CD163 is likely non-specific due to increased lysosomal activity and does not indicate true histiocytic or epithelial differentiation. We recommend that in the absence of overt high-grade features or admixture with conventional diffuse astrocytoma on intra-operative smear and frozen section, it may be advisable to wait to confirm the diagnosis on paraffin section histology and immunohistochemical stains before proceeding with definitive tumor resection. This diagnostic approach will prevent over-treatment by resection of non-neoplastic mimics of GCA.